Importance of Parameter and Climate Data Uncertainty for Future Changes in Boreal Hydrology. Issue 8 (4th August 2021) - Marshall, Adrienne M.; Link, Timothy E.; Flerchinger, Gerald N.; Lucash, Melissa S.
Abstract: Soil moisture and evapotranspiration (ET) are important components of boreal forest hydrology that affect ecological processes and land‐atmosphere feedbacks. Future trends in soil moisture in particular are uncertain. Therefore, accurate modeling of these dynamics and understanding of concomitant sources of uncertainty are critical. Here, we conduct a global sensitivity analysis, Monte Carlo parameterization, and analysis of parameter uncertainty and its contribution to future soil moisture and ET uncertainty using a physically based ecohydrologic model in multiple boreal forest types. Soil and plant hydraulic parameters and LAI have the largest effects on simulated summer soil moisture at two contrasting sites. In future scenario simulations, the selection of parameters and global climate model (GCM) choice between two GCMs influence projected changes in soil moisture and ET about as much as the projected effects of climate change in the less sensitive GCM with a late‐century, high‐emissions scenario, though the relative effects of parameters, GCM, and climate vary among hydrologic variables and study sites. Saturated volumetric water content and sensitivity of stomatal conductance to vapor pressure deficit have the most statistically significant effects on change in ET and soil moisture, though there is considerable variability between sites and GCMs. The results of this study provide estimates of: (a) parameter importance and statistical significance for soil moisture modeling, (b) parameter values for physically based soil‐vegetation‐atmosphere transfer models in multiple boreal forest types, and (c) the contributions of uncertainty in these parameters to soil moisture and ET uncertainty in future climates. Plain Language Summary: Future changes in soil water content and evapotranspiration (ET) in boreal regions will influence forest dynamics, permafrost thaw rates and have the potential to alter feedbacks between the land surface and the atmosphere, potentially influencing regional climate dynamics. These changes are uncertain and difficult to model because of the complexity of the boreal ecological and hydrological systems. In this study, we conduct experiments with a hydrological model to better understand which parameters most influence soil water content and ET, how much uncertainty these parameters contribute, and how specific parameter values affect whether soils become wetter or drier and by how much. We find that the parameters that control how tightly soils retain water and how much plants close their stomata and hence reduce transpiration in response to dry conditions, have the largest influences. Interactions between parameters are also important. Even when these parameter values are constrained by model performance in comparison with observations, parameter choice can determine whether soils become wetter or drier in future conditions. These findings suggest that modelers should carefully consider how parameter selection influences simulated future hydrologic conditions and highlight specific parameters that are worthy of further attention. Key Points: Modeled summer soil moisture at rooting depth is most sensitive to soil and plant hydraulic parameters and parameter interactions. Parameter uncertainty affects projected change in evapotranspiration and θ VWC about as much as climate change or choice between two global climate models. We present parameter values useful for hydrologic modeling in multiple boreal forest types while quantifying the impacts of equifinality.